(3TQM GdJUQja GdYRj ddJaJGRGfjs - (3GdJaJGRGfj, SYO GdOjf, eSYhO Hf YeQ Hf YHO Gddg GdJaJGRGfj, J (B793(3g` (B1390(3es
(3ChdgG (B:s
(3ChdgG(B: (3Ef CQhi RgQ jNQL aj QjGV GdcdGe ef GdCceGe hGHgi NHQ jMGc HHfGf hGSfGf GdCbdGe MeO Gddg (B... (3deG cGf ef GdhGLH Ydi WGdH dTjA Cf jJUhQ Pdc GdTjA jchf Ydi HUjQIs
(3BNQgG (B:s
(3BNQgG(B: (3hgPG aj GdKdGKj GdeLQO GdPj dG JGA ajg hGeG ZjQg aGdfhY efg cGdeQI HdG aQb aj GddaX hGdaGQb hGdbQGFf GdNGQLjI Jbhd QMeI hGMOI ddeQI hdbjWI hfMhgG ddfhY hGfWdGbI hGMOI ddeQI GdhGMOI hMSfI hbHjMI Ch ZjQgeG ddfhY (B.. (3hGddg GdeSJYGfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B/ (3L (B7: 219s
(3cTa GdXfhf, L (B2: 1139s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdUQas